Birgittine circles: people and saints in the medieval world - Andersson, Elin; Hedström, Ingela; Åkestam, Mia (KVHAA Konferenser, 2023)
The concept of 'circles' is applied to Birgittine networks, the importance of individuals, places, and objects associated with the Birgittine Order, as well as to ideas, physical objects, travels, and exchange between different orders. The ten contributions collected in this volume reflect the interdisciplinary research on Birgitta's influence on late medieval culture and the Birgittine Order. Some studies focus on material sources from Vadstena, emphasizing the social significance and value of objects and material culture, whereas other studies focus on literary sources and the reception of Birgitta and her Revelationes. The spread of the Birgittine Order and Birgittine spirituality linked to objects and texts is explored in places as widely separated as southern Europe and northern Sweden